Relationship between non‐standard work arrangements and work‐related accident absence in Belgium. Issue 2 (20th March 2017) - Alali, Hanan; Braeckman, Lutgart; Van Hecke, Tanja; De Clercq, Bart; Janssens, Heidi; Wahab, Magd Abdel
Abstract : Objectives: The main objective of this study is to examine the relationship between indicators of nonstandard work arrangements, including precarious contract, long working hours, multiple jobs, shift work, and work‐related accident absence, using a representative Belgian sample and considering several sociodemographic and work characteristics. Methods: This study was based on the data of the fifth European Working Conditions Survey (EWCS) . For the analysis, the sample was restricted to 3343 respondents from Belgium who were all employed workers. The associations between non‐standard work arrangements and workrelated accident absence were studied with multivariate logistic regression modeling techniques while adjusting for several confounders. Results: During the last 12 months, about 11.7% of workers were absent from work because of work‐related accident. A multivariate regression model showed an increased injury risk for those performing shift work (OR 1.546, 95% CI 1.074‐2.224). The relationship between contract type and occupational injuries was not significant (OR 1.163, 95% CI 0.739‐1.831). Furthermore, no statistically significant differences were observed for those performing long working hours (OR 1.217, 95% CI 0.638‐2.321) and those performing multiple jobs (OR 1.361, 95% CI 0.827‐2.240) in relation to work‐related accident absence. Those who rated their health as bad, low educated workers, workers from the construction sector, and those exposed to biomechanical exposure (BM) were more frequent victims of workrelated accident absence. No significant gender difference was observed. Conclusion: Indicators of nonstandard work arrangements under this study, except shift work, were not significantly associated with workrelated accident absence. To reduce the burden of occupational injuries, not only risk reduction strategies and interventions are needed but also policy efforts are to be undertaken to limit shift work. In general, preventive measures and more training on the job are needed to ensure the safety and well‐being of all workers.